Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/dvdy.22087
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptors exhibit cell‐autonomous functions in cranial neural crest cells

Abstract: Previous work has emphasized the crucial role of retinoic acid (RA) in the ontogenesis of the vast majority of mesenchymal structures derived from the neural crest cells (NCC), which migrate through, or populate, the frontonasal process and branchial arches. Using somatic mutagenesis in the mouse, we have selectively ablated two or three retinoic acid receptors (i.e., RARa/RARb, RARa/RARc and RARa/RARb/ RARc) in NCC. By rigorously analyzing these mutant mice, we found that survival and migration of NCC is norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…Whereas RAR and RAR act cell-autonomously in NCCs, RAR is dispensable (Dupe and Pellerin, 2009). A local source of RA in the chick rostral head coordinates FNP morphogenesis through Fgf8 and Shh induction in the forebrain and facial ectoderm (Schneider et al, 2001) (Fig.…”
Section: Retinoic Acid Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas RAR and RAR act cell-autonomously in NCCs, RAR is dispensable (Dupe and Pellerin, 2009). A local source of RA in the chick rostral head coordinates FNP morphogenesis through Fgf8 and Shh induction in the forebrain and facial ectoderm (Schneider et al, 2001) (Fig.…”
Section: Retinoic Acid Signallingmentioning
confidence: 99%
“…The double inactivations of RAR and RAR, or RAR and RAR, induce PA hypoplasia and NCC-derived cartilage malformations (Dupe et al, 1999;Lohnes et al, 1994;Mendelsohn et al, 1994;Wendling et al, 2000). However, the endoderm could be the primary target of RA action in mediating morphogenesis of PA2 and more posterior arches , as RARs are mostly dispensable in cranial NCCs (Dupe and Pellerin, 2009). Not only RA deficiency, but also exogenous RA excess during pregnancy or the inactivation of the cytochrome P450 (Cyp) RA-degrading enzymes induce teratogenesis in the craniofacial region (Abu-Abed et al, 2001;Maclean et al, 2009;Mulder et al, 2000;Reijntjes et al, 2007;Uehara et al, 2007).…”
Section: Retinoic Acid Signallingmentioning
confidence: 99%
“…Frontonasal agenesis has been reported in compound RAR null mutant mice [97] and RBP null mutant mice on a vitamin A-deficiency diet [110]. Dupe and Pellerin recently showed that selective ablation of RARα and RARγ subtypes using the Wnt1-Cre promoter leads to agenesis of the frontonasal skeletal elements, but does not appear to adversely affect the early survival and migration of neural crest cells [227]. Deletion of all three RAR subtypes using the selective promoter produces a similar phenotype, indicating that RARα and RARγ act cell-autonomously in neural crest cells to direct morphogenesis of these skeletal elements.…”
Section: Vitamin a And Embryonic Developmentmentioning
confidence: 99%
“…These include (i) the ''first heart field'' or cardiac crescent formed from mesoderm emerging from the primitive streak (Garcia-Martinez and Schoenwolf, 1993;Tam et al, 1997); (ii) the ''second heart field'' originating from pharyngeal mesoderm (Buckingham et al, 2005); (iii) the (pro)epicardium, a population originating and giving rise to coronary vasculature, myocardial fibroblasts and to a distinct cardiomyocytic lineage (Cai et al, 2008;Zhou et al, 2008), and (iv) the ''cardiac'' neural crest, a subset of post-otic neural crest cells migrating through the third to sixth branchial arches and participating to the development of the aortic arches and aorticopulmonary septum (reviewed by Rochais et al, 2009). All these lineages have been reported to be influenced by embryonic RA (Hochgreb et al, 2003;Ryckebusch et al, 2008;Sirbu et al, 2008;Dupe and Pellerin, 2009), although recent studies implicate the second heart field (Ryckebusch et al, 2008;Sirbu et al, 2008) and the epicardium (Merki et al, 2005;Lin et al, 2010) as the main sites of RA signaling.…”
Section: Branchial Arches and Heartmentioning
confidence: 99%